Chemical characteristics of atmospheric precipitation and their effects on microbial diversity in Baotou, China - Wang, Lili; Yang, Yuping; Gao, Li; Gao, Zhichun (Frontiers in Microbiology, 2025)
IntroductionExisting studies on the coupling of atmospheric precipitation chemistry and microbial communities have long focused on humid regions, while overlooking the unique “sand-dust-agriculture-industry” compound pollution in arid/semi-arid industrial cities—creating a critical knowledge gap. This study aimed to systematically explore the interactive mechanisms, community assembly processes, and ecological/health implications of precipitation-associated microbes in Baotou, a typical heavy-industry hub in northern China.MethodsPrecipitation samples were collected from May to August 2023 and analyzed for chemical ions (Ca2+, NH₄+, SO₄2−, etc.) and microbial communities via ion chromatography and high-throughput sequencing of 16S/18S rRNA genes. Community assembly processes were assessed using null model analyses (NST, iCAMP), and microbial functions were predicted via FAPROTAX and FUNGuild.ResultsBaotou’s precipitation exhibited a neutral pH (7.04 ± 0.14) but abnormally high ion loading (795.09 ± 94.68 μeq·L−1), dominated by Ca2+, NH₄+, and SO₄2−, reflecting mixed dust, agricultural, and industrial sources. Microbial community assembly was predominantly stochastic (drift + dispersal limitation >79% in bacteria and >86% in fungi), with fungi showing significantly broader niche width and overlap than bacteria (p<0.05). Functionally, bacteria were primarily involved in carbon and nitrogen cycling, whereas fungi displayed balanced saprotrophic (48.03%) and pathogenic (48.24%) traits. Fungal pathogens (e.g., Cladosporium, Alternaria) were significantly more abundant than bacterial pathogens, forming a distinct “fungal-dominated” health risk profile.DiscussionThe dominance of stochastic assembly and the functional divergence between bacteria and fungi underscore unique microbial adaptive strategies under compound pollution stress in arid industrial atmospheres. The high abundance of allergenic fungal pathogens highlights significant public health risks, especially during warm seasons. This study provides a novel framework for understanding precipitation chemistry-microbe interactions in arid industrial environments, offering critical insights for regional air quality management and health risk assessment.